Pengaruh Ukuran Perusahaan, Profitabiltas dan Leverage terhadap Kebijakan Dividen pada Perusahaan Sektor Perbankan yang Terdaftar pada Bursa Efek Indonesia (BEI) Periode 2019-2022 - Husin, Muhammad Fajrin; Dama, Hais; Ishak, Idham Masri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The Effect of Firm Size, Profitability and Leverage on Dividend Policy in Banking Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 Period. The populations used in this study were all Banking Sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. In the meantime, the samples, which were 12 baking companies, were determined through purposive sampling. The data collection technique in this study used the documentation technique, namely searching for financial statement data published by the company from 2019 to 2022. Then, the analysis test used in testing this study was multiple linear regression analysis. The study findings revealed that the firm size ratio affected dividend policy partially, indicating that the increasing firm size would increase the dividends distributed. Subsequently, the profitability ratio did not possess a partial effect on dividend policy because the company prioritized the sources of funds obtained to finance the company's growth rather than distributing dividends. Lastly, the leverage ratio also did not possess a partial effect on dividend policy. Meanwhile, simultaneously, firm size, profitability, and leverage affected dividend policy with a determination coefficient of 19.4%, while the remaining 70.6% was affected by other variables not examined in this study.